The Pattern of Legal Aid Institutions Towards Protection for Victims of Sexual Violence in Medan City - Rasina Padeni Nasution (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
North Sumatra Women's and Children's Empowerment Service data from 2019 recorded 216 cases. In 2020, sexual violations or criminal demonstrations of sexual viciousness increased to 1,013 cases, and by December 2021, the number dropped to 953 cases in the city of Medan. The government has continued its efforts to protect its citizens who are vulnerable to sexual violations or criminal demonstrations of sexual viciousness since the birth of Act No. 12 of 2022, involving legal aid institutions in providing protection to victims. The purpose of this research is to learn the legal instruments and patterns of protection of the Legal Aid Institute for victims of sexual violations or criminal demonstrations of sexual viciousness. The research method used is juridical through case study approaches and conceptual approaches. Data collection techniques by means of observations, interviews, and field documentation are qualitatively processed and analyzed descriptively. Research results show that legal instruments for the protection of victims of sexual violations or criminal demonstrations of sexual viciousness are not only in the Criminal Code but also in the Penal Code of Sexual Violence and the Child Protection Act. The protection pattern carried out by the Legal Assistance Agency is through the standard operational processes of internal procedures with the approach of structural legal assistance systems and structural gender legal assistance.